Urbanization and Transformation in Tribal Communities: A Study of the Gujjar and Bakarwal Tribes of Doda District (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This study examines urbanisation and technological integration’s socio-cultural and economic impacts on the Gujjar and Bakarwal tribe in the Doda region of Jammu and Kashmir. Using a qualitative research approach, data was collected through household surveys, focus group discussions, and in-depth interviews in two selected villages with significant Bakarwal populations. Findings reveal a complex interplay between traditional livelihoods and modern socio-economic pressures. Urban migration, driven by the search for stable income, has reshaped family structures and weakened traditional practices. While technology has facilitated communication and offered economic opportunities, it has also contributed to a generational divide and reduced cultural engagement among the youth. Government support mechanisms, although beneficial, are insufficient in addressing the broader socio-cultural challenges. The study underscores the need for adaptive strategies integrating traditional knowledge with modern advancements to ensure sustainable development and cultural preservation within tribal communities.